Dampak Penggunaan Gadget dan Tingkat Kontrol Orang Tua Terhadap Produktivitas Belajar pada Remaja - Siti Zahra Bulantika; Sa'adah Sa'adah; Indra Lacksana; M.Zuhdi Zainul Majdi; Sulma Mafirja (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2020)
Learning productivity is very important for teenagers, especially students, because it will have an effect on future success. The low productivity of students is caused by several factors, namely external and internal. The use of gadgets and the level of parental control are factors in student learning productivity. This study aims to determine the impact of using gadgets and the level of parental control on learning productivity in adolescents. This research is a quantitative research that uses the explanatory method. The population of this study were students of class IX MTS N 1 Bandar Lampung. The sampling technique used was Proportional Stratified Random Sampling and 63 respondents were selected. Hypothesis testing was carried out using Multiple Linear Regression Test. The results show that there is an effect of the intensity of the impact of using gadgets and the level of parental control on learning productivity in adolescents. This research is expected to be able to provide understanding for all parties, from students, teachers and also parents so that they can play a role, maximize or utilize the use of gadgets for things that have a positive impact.